REALISATION, INSTANTIATION AND INDIVIDUATION: SOME THOUGHTS ON IDENTITY IN YOUTH JUSTICE CONFERENCING - Martin, J R (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2009)
This paper is concerned with identity and how it can be modelled in SFL, with special reference to the roles played by young offenders in Australia’s youth justice conferences. These conferences function as a restorative justice alternative to courtroom-based retributive justice. It is proposed that a hierarchy of individuation be established, alongside and complementing realisation and instantiation, responsible for users of language, the ways in which semiotic resources are allocated to them, and the ways in which they use these resources to form social groups. This hierarchy is briefly explored in relation to teenage identity